2020
DOI: 10.1080/20013078.2020.1792683
|View full text |Cite
|
Sign up to set email alerts
|

In vivo identification of apoptotic and extracellular vesicle‐bound live cells using image‐based deep learning

Abstract: The in vivo detection of dead cells remains a major challenge due to technical hurdles. Here, we present a novel method, where injection of fluorescent milk fat globule-EGF factor 8 protein (MFG-E8) in vivo combined with imaging flow cytometry and deep learning allows the identification of dead cells based on their surface exposure of phosphatidylserine (PS) and other image parameters. A convolutional autoencoder (CAE) was trained on defined pictures and successfully used to identify apoptotic cells in vivo. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 81 publications
4
42
0
Order By: Relevance
“…To determine whether PS is exposed on degenerating myelin sheaths, we used a recently described PS reporter that can be applied in vivo . We took advantage of secreted glycoprotein MFG-E8, which specifically recognizes PS and, when fused to EGFP, can be delivered as a recombinant protein for PS detection (Kranich et al, 2020). Because injections of recombinant protein into the spinal cord may induce damage, we modified this approach by expressing the genetically encoded secreted MFG-E8-EGFP in microglia (Figure 3I,J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether PS is exposed on degenerating myelin sheaths, we used a recently described PS reporter that can be applied in vivo . We took advantage of secreted glycoprotein MFG-E8, which specifically recognizes PS and, when fused to EGFP, can be delivered as a recombinant protein for PS detection (Kranich et al, 2020). Because injections of recombinant protein into the spinal cord may induce damage, we modified this approach by expressing the genetically encoded secreted MFG-E8-EGFP in microglia (Figure 3I,J).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain pTol2-UAS:MFG-E88-C1C2-EGFP, we first cloned pME-MFG-E8-C1C2-EGFP by PCR amplification of the mouse MFG-E8 C1 and C2 domain (insert) and of the middle entry vector backbone (vector), using Q5 polymerase (New England Biolabs Inc). Fragments were generated with the following primers (template plasmids indicated in brackets): insert fragment (pD2523-mMFG-E8_C1C2-EGFP, kind gift of Jan Kranich(Kranich et al, 2020)): 5’-ATGCAAGTCTCTAGGGTAC-3’ (fwd) and 5’-CTTATAAAGTTCATCCATGCCA-3’ (rev), vector fragment (pME-KalTA4GI): 5’-GCATGGATGAACTTTATAAGTAAACCCAGCTTTCTTG-3’ (fwd) and 5’-AGTACCCTAGAGACTTGCATGGTGGCGGCAGCCT-3’ (rev). This was followed by a 2-fragment Gibson assembly, using the NEBuilder® HiFi DNA Assembly Cloning Kit (New England Biolabs, Inc.) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have demonstrated that MFG-E8 secretory glycoprotein is highly expressed in the different types of EVs. By its discoidin domain MFG-E8 protein associates with PS exposed on the membranes and this property has already been used for the in vivo identification of apoptotic and EV-bound cells [29]. EVs used in our study expressed high levels of MFG-E8 protein (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Milk fat globule-epidermal growth factor-factor VIII (MFG-E8) is a secretory glycoprotein expressed in microglia [27]. MFG-E8 also associates with EVs by binding to the phosphatidylserine (PS) [28,29]. Indeed, EVs derived from the SHEDs express high levels of MFG-E8 [22] (Fig.…”
Section: Evs Promote Association Between Mfg-e8 and P2x4 Receptor Proteins In Human Microgliamentioning
confidence: 99%
“…Even realistic presentation of the proteins in their native cellular microenvironment has been achieved through cryo-electron tomography (cryo-ET) ( Danev et al, 2019 ; Kuwana, 2019 ; Wang et al, 2019a ). Also, flow cytometry is regarded as a preferred method since it is sensitive, fast and multifaceted, and this method is constantly improving and being integrated into clinical applications, such as image-based flow cytometry ( Kranich et al, 2020 ). So many methods also show great potential in research and clinical applications, such as real-time fluorometry, or PET and single-photon emission computed tomography (SPECT) with specific tracers, multicolor labeling and sophisticated morphometric analysis, etc.…”
Section: Conclusion and Perspectivementioning
confidence: 99%